4IR technologies in the Israel Defence Forces: blurring traditional boundaries. Issue 4 (7th June 2021) - Evron, Yoram
ABSTRACT: This paper explores how Fourth Industrial Revolution (4IR) technologies obscure the traditional boundaries associated with the military realm. As the first examination of the conditions underlying the assimilation of 4IR technologies in Israel's armed forces, this paper makes several contributions. It expands the knowledge on the military assimilation of 4IR technologies and describes the interaction between military doctrine and technology using current evidence. It also enriches the evolving discussion on the strategic effect of emerging technologies. Finally, it demonstrates how emerging technologies involve neither straightforward spinoff or spin-on processes but a reciprocal transfer of know-how between the military and civilian sectors.